APPEAL FOR DISPOSING GARBAGE IN THE CITY OF PADANG (A PRAGMATIC STUDY) - Arifan, Arifan; Aslinda, Aslinda; Revita, Ike (Universitas PGRI Sumatera Barat, 2023)
This study discusses the utterance of an appeal for disposing garbage in the city of Padang. The problems studied are what are the modes, types of utterances, how do the speakers urge the interlocutors to dispose of the trash, and what are the factors that influence the utterances of the appeal for disposing the trash in the city of Padang. The aim is to explain the mode, type of speech, how the speaker urges the interlocutor to dispose of the trash, and what are the factors that influence the utterance of the appeal for disposing the trash in the city of Padang. This research is a qualitative research that is descriptive in nature by collecting data using the listening method and analyzing data using the matching method. The findings of this study indicate that the mode used is declarative mode, interrogative mode, and imperative mode. The types of speech used include direct literal speech acts, direct non-literal speech acts, literal indirect speech acts, and non-literal indirect speech acts. The way the speaker urges the interlocutor to throw garbage in the city of Padang is done by using imperative sentences, using imperative sentences, using imperative statements, using information formulas, using interrogative sentences, praying, forbidding, inviting, threatening, using negations, saying thank you. , and using statements. Influencing factors are speaker factors which include age, education, and gender, speech atmosphere factors which include formal and informal, and place of speech factors.